ARTS SERVICE IMPROVEMENT FOR STUDENT SELF DEVELOPMENT IN ELEMENTARY SCHOOL - Ernawati; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This descriptive qualitative research is a fact that is revealed through the currenteducational phenomenon. Improving Arts Services for Self-DevelopmentParticipants at SDN 9 Tapaktuan, South Aceh District seeks to plan andorganize student self-development activities in the arts to obtain results that arein accordance with the wishes of the school and progress in the arts school atSDN 9, South Aceh District. The active role and cooperation of all schoolmembers in fostering students through extracurricular activities, especially inthe arts. Acehnese traditional dance is an integral part of Indonesia's culturalwealth. The aim of the research is to benefit the development of Acehnesetraditional dance in shaping character, creativity and love for local culture. Theimplementation of enhanced services includes introducing traditional dancemovements and elements, understanding dance philosophy, and creatingcollaborative dance works with a contemporary touch.